Analisis Student Engagement Dan Burnout Pada Mahasiswa Politeknik Negeri Manado - Christine Adriani Karambut; Jacob Tateol Silangen Makapedua; Daisy Iriany Erny Sundah; Grace Joice Silvana Neltje Rumimper (Universitas Merdeka Madiun, 2024)
The number of attrition increases every year so the competition for job seekers must become increasingly competitive. Although the cumulative achievement index (GPA) is not an absolute guarantee to be used as a reference in looking for work. However, GPA is the administration's initial selection in recruiting employees, so students must have a strategy to be able to achieve a high GPA. One of the efforts made to achieve a high GPA is with good academic achievement. Learning achievement is influenced by internal and external factors. External factors are factors that come from outside the student. Meanwhile, internal factors come from within the student, including engagement and burnout. The aim of this research is to determine the level of student engagement and academic burnout of students. The population in this study were students from the Business Administration Department of Manado State Polytechnic with a sample of 100 students. The sampling method in this research is convenience sampling. The data analysis used is descriptive statistical analysis. The results of this research state that student engagement is in the high category. The highest average score is a feeling of pride among students studying at the Manado State Polytechnic Campus. Meanwhile, the lowest average score is that students are forced to carry out all learning activities on campus because it is considered less interesting. Meanwhile, the level of student burnout is in the medium category. The highest average burnout score is that talking about studies is boring for students. Meanwhile, the lowest students can usually manage the workload related to ongoing studies well.